Handbook of research on algae as a sustainable solution for food, energy, and the environment - El-Sheekh, Mostafa; Abdullah, Norhayati; Ahmad, Imran, 1982- (Practice, progress, and proficiency in sustainability (PPPS) book series., 2022)
"This book provides an opportunity to the readers to understand about the biological and biotechnological processes going on in the cultivation and harvesting of algae, DNA sequencing, and genomics of algae, giving detailed insight into various applications of algal biomass in agriculture, food, feed, and medicines"--